2015
DOI: 10.1128/aac.04338-14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of First-Line Antituberculosis Drugs in HIV-Infected Children with Tuberculosis Treated with Intermittent Regimens in India

Abstract: The objective of this report was to study the pharmacokinetics of rifampin (RMP), isoniazid (INH), and pyrazinamide (PZA) in HIV-infected children with tuberculosis (TB) treated with a thrice-weekly anti-TB regimen in the government program in India. Seventy-seven HIV-infected children with TB aged 1 to 15 years from six hospitals in India were recruited. During the intensive phase of TB treatment with directly observed administration of the drugs, a complete pharmacokinetic study was performed. Drug concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…Ramachandran et al found similar results with only 10 % achieving concentrations [8 lg/mL across all age groups studied but specifically that all children aged \3 years did not achieve concentrations within the target range [14]. A more recent study by Ramachandran found 97 % of children (all HIV positive) did not achieve target concentrations [13]. Thee et al attempted to study the effect of dose on rifampin concentrations and noted that with the standard 10 mg/kg dosing, only 45 % had rifampin C max values [8 lg/mL but this number increased to 73 % after dosing based on 15 mg/kg [22].…”
Section: Rifampinsupporting
confidence: 59%
“…Ramachandran et al found similar results with only 10 % achieving concentrations [8 lg/mL across all age groups studied but specifically that all children aged \3 years did not achieve concentrations within the target range [14]. A more recent study by Ramachandran found 97 % of children (all HIV positive) did not achieve target concentrations [13]. Thee et al attempted to study the effect of dose on rifampin concentrations and noted that with the standard 10 mg/kg dosing, only 45 % had rifampin C max values [8 lg/mL but this number increased to 73 % after dosing based on 15 mg/kg [22].…”
Section: Rifampinsupporting
confidence: 59%
“…In adult RMP dose-escalation studies of up to 35 mg/kg/day for 2 weeks, higher doses showed a disproportionate plasma exposure increase with dose and a greater fall in bacterial load (48). Multiple factors influence the relationship between drug concentrations and TB treatment outcome, including M. tuberculosis genotype, gene polymorphisms, extent of TB disease, bacillary burden, and immune status, including HIV infection status (46). A limitation of our study is that the study drug was administered only on the pharmacokinetic day, while routine drugs were used for the 6-month treatment; this limits the interpretation of drug concentrations on TB treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent elimination of first-line antituberculosis drugs has been shown, with lower exposures documented in younger children for RMP (10,14,40), INH (14,40,46), PZA (8,14), and EMB (42). These findings have mainly been attributed to the more rapid clearance of drugs and to a relatively larger liver-to-body size ratio.…”
Section: Discussionmentioning
confidence: 99%
“…While our study was not designed to investigate the relationship between pharmacokinetics and TB treatment outcome, the lower median plasma exposure and C max of rifampin and ethambutol in the HIV-coinfected patients is concerning and raises the question of whether inadequate drug pharmacokinetics is a contributor to the higher risk of an unfavorable treatment response. At least one group reported a relationship between lower rifampin and pyrazinamide C max and unfavorable TB treatment outcome (death, failure, and default) in HIV-infected children (19) and in a combined group of HIV-infected and uninfected children in India treated with a thrice-weekly regimen (32). Thus, strategies to improve TB treatment outcomes in children, especially with HIV coinfection, should include optimized dosages of rifampin, pyrazinamide, and ethambutol.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, low plasma exposure to the rifamycins in the setting of intermittent therapy in HIV-infected patients with TB has been associated with treatment failure and emergence of rifampin resistance (16)(17)(18). While there are limited data on the relationship between pharmacokinetic (PK) parameters and pharmacodynamics in children, one study from India reported an association between low plasma maximum concentrations (C max ) of rifampin and pyrazinamide and unfavorable clinical outcomes in HIV-infected children (19).…”
mentioning
confidence: 99%